Analisis Pemilihan Metode, Strategi, dan Pendekatan Pembelajaran dalam Upaya Meningkatkan Kualitas Belajar Peserta Didik - Muhammad Indra Data; Yuniar Mujiwati; Listyanti, Berliana Fajar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The selection of appropriate learning methods, strategies, and approaches is a crucial factor in improving the quality of student learning. Mismatches in the application of these three components can result in low student engagement and suboptimal achievement of learning objectives. This article aims to analyze the selection of learning methods, strategies, and approaches in an effort to improve the quality of student learning. This study uses a qualitative approach with a literature review design. Data were obtained through study documentation of various relevant written sources, including books, scientific articles, and journals accessed through Google Scholar. Data analysis was conducted descriptively and qualitatively by reviewing, comparing, and synthesizing concepts, theories, and research findings related to learning methods, strategies, and approaches. The results of the study indicate that the appropriate selection of learning methods, strategies, and approaches tailored to student characteristics, learning objectives, and learning contexts can improve student engagement, understanding, and learning outcomes. Therefore, teachers need to have a comprehensive understanding in determining learning methods, strategies, and approaches to create an effective and meaningful learning process.